Predictive Factors for Drain Placement After Laparoscopic Cholecystectomy - Calini, Giacomo; Brollo, Pier Paolo; Quattrin, Rosanna; Bresadola, Vittorio (Frontiers in Surgery, 2022)
Purpose Currently, surgical drainage during a laparoscopic cholecystectomy (LC) is still placed in selected patients. Evidence of the non-beneficial effect of the surgical drain comes from studies with a heterogeneous population. This preliminary study aims to identify any clinical, demographic, or intraoperative predictive factors for a surgical drain placement during LC as the first step to identify population for a prospective randomized study. Method The study was conducted in a single referral center and academic hospital between 2014 and 2018. Patients who underwent unconverted LC were divided into two groups: Group A (drain) and Group B (no drain). We explored baseline, preoperative, intraoperative characteristics, and postoperative outcomes. Results Between 409 patients who underwent LC: 90 (22%) patients were in Group A (drain). Age >64 years, male sex, cholecystitis, Charlson comorbidity index (CCI) ≥ 1, experienced surgeon, intraoperative technical difficulties, need for an additional trocar, operative time >60 min, and estimated blood loss >10 ml were predictive factors at univariate analysis. While at multivariate analysis, cholecystitis (odds ratio [OR]: 2.8, 95% CI:1.5–5.1; p < 0.001), CCI ≥ 1 (OR:1.9, 95% CI:1.0–3.5; p = 0.05), intraoperative technical difficulties (OR: 3.6, 95% CI:1.8–6.2; p < 0.001), need of an additional trocar (OR: 2.5, 95% CI: 1.4–4.4; p < 0.005), and estimated blood loss >10 ml (OR: 3.0, 95% CI:1.7–5.3; p < 0.0001) were predictive factors for a surgical drain placement during LC. Conclusions This study identified predictive factors that currently drive the surgeons to a surgical drain placement after LC. Randomized prospective studies are needed to define the use of drain placement in these selected patients.